3-Methoxysalicylaldehyde 4-methoxybenzoyl-hydrazone monohydrate - Huo, L.H.; Ng, S.W.; Zain, Sharifuddin Md; Zhao, J.G.; Zhao, H.; Gao, S. (International Union of Crystallography, 2004)
The title compound, C16H16N2O 4·H2O, crystallizes as a monohydrate in which the water molecule forms bifurcated hydrogen bonds to the hydroxyl and methoxy O atoms of the methoxysalicyldehyde portion of the Schiff base. The molecule is approximately planar; hydrogen-bonding interactions involving the amino group and the water molecule give rise to a layer structure. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.